Produk Ekonomi Kreatif Berbasis Hak Kekayaan Intelektual Sebagai Objek Jaminan Kredit Perbankan - Syafrida Syafrida; Ralang Hartati; Mangisitua Marbun; Hasudungan Sinaga (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Advances in information and communication technology have had the impact of increasing the development of the creative economy. Products of creative economy actors based on Intellectual Property Rights can be used as collateral for credit. The problem is what are the criteria for creative economic products based on Intellectual Property Rights that can be used as collateral for bank credit and how is the assessment carried out by banks on objects of credit guarantees in the form of creative economic products based on Intellectual Property Rights? The research approach is in the form of a statutory approach and a conceptual approach. The results of the study state that the criteria for creative economic products that can be used as bank credit guarantee objects are IPR-based creative economic products that are registered and registered with the Director General of Intellectual Property Rights of the Ministry of Law and Human Rights and are reputable, have economic value, are self-managed or transferred to other parties.Keywords: Creative Economy; Intellectual property rights; Credit Guarantee Object AbstrakKemajuan teknologi informasi dan komunikasi membawa dampak meningkatnya perkembangan ekonomi kreatif. Produk pelaku ekonomi kreatif berbasis Hak Kekayaan Intelektual dapat dijadikan objek jaminan kredit. Permasalahannya apa kriteria produk ekonomi kreatif berbasis Hak Kekayaan Intelektual dapat dijadikan objek jaminan kredit perbankan dan bagaimana penilaian yang dilakukan oleh bank terhadap objek jaminan kredit berupa produk ekonomi kreatif berbasis Hak Kekayaan Intelektual? Pendekatan penelitian berupa pendekatan perundang-undangan dan pendekatan konseptual. Hasil penelitian menyatakan bahwa kriteria produk ekonomi kreatif yang dapat dijadikan objek jaminan kredit bank adalah produk ekonomi kreatif berbasis HKI yang tercatat dan terdaftar pada Dirjen HKI Kemenkum HAM dan bereputasi, bernilai ekonomi, dikelola sendiri maupun dialihkan kepada pihak lain.Kata kunci: Ekonomi Kreatif; Hak Kekayaan Intelektual; Objek Jaminan Kredit